The Pangeran and the saints: The historical inflection of a mid 19th-century Ḥaḍramī mausoleum in East Java, Indonesia. Issue 130 (1st September 2016) - Alatas, Ismail Fajrie
ABSTRACT: This article charts the history of a mid 19th-century Ḥaḍramī mausoleum in Surabaya, East Java. Officially known as the mausoleum of the Ḥaḍramī saints Muḥammad b. ʿAydarūs al-Ḥabashī (d.1919) and Muḥammad b. Aḥmad al-Miḥḍār (d.1926), the site has been a popular destination of Indonesian Muslim pilgrims. A close inspection of the inscriptions on the other tombstones in the mausoleum, however, reveals that the edifice was actually built in honour of Pangeran Ḥasan b. ʿUmar al-Ḥabashī (d.1854), a wealthy Ḥaḍramī entrepreneur and diplomat who served the Dutch colonial authorities. This article observes the processes through which the family mausoleum of the Pangeran became known as the mausoleum of two saintly figures. It argues that the interment of the saints in the mausoleum initiated discursive and liturgical developments that resulted in its transfiguration into a devotional site with new histories that gradually eclipsed its earlier identity. Such developments included the production of hagiographic texts and the institutions of ritual practice and commemorations, all of which inadvertently neglected the mausoleum's prior history and inflected its identity.